2022
DOI: 10.3389/fimmu.2022.857692
|View full text |Cite
|
Sign up to set email alerts
|

TnP Peptide Suppresses Experimental Autoimmune Encephalomyelitis (EAE) in a Preclinical Mouse Model

Abstract: TnP is a family of patented synthetic peptides which is in a preclinical development stage with valuable potential therapeutic indication for multiple sclerosis (MS), an autoimmune demyelinating disease of the central nervous system (CNS). The use of a preclinical animal model, such as experimental autoimmune encephalomyelitis (EAE) has deepened our knowledge of the immunomodulatory functions of TnP as a drug. We have shown that TnP possesses a disease suppressive function in EAE, ameliorating disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, we demonstrated that EAE mice treated prophylactically with subcutaneously or orally applied Tn P exhibited protection against the development of CNS symptoms and inflammation similar to betaseron or fingolimod, but more efficiently than both in the long-term control of neuronal degeneration. Compared to glatiramer, Tn P was more efficient in switching off pathogenic cells as macrophages and microglia, and in activating regulatory cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that EAE mice treated prophylactically with subcutaneously or orally applied Tn P exhibited protection against the development of CNS symptoms and inflammation similar to betaseron or fingolimod, but more efficiently than both in the long-term control of neuronal degeneration. Compared to glatiramer, Tn P was more efficient in switching off pathogenic cells as macrophages and microglia, and in activating regulatory cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%